Perbandingan batas usia menikah di Indonesia dan negara lain dalam perspektif teori Hukum Progresif - Qoiriyah, Alfina (Maliki Interdisciplinary Journal, 2024)
The age limit for marriage is an essential issue in family law. A marriage age limit that is too low can cause various problems, such as domestic violence, dropping out of school, and stunting. From the perspective of progressive legal theory, the age limit for marriage must be formulated by considering aspects of justice and welfare. A comparison of the marriage age limit in Indonesia and other countries shows diversity. In Indonesia, the legal age for marriage is 19 years for men and women. Meanwhile, in several other countries, the marriage age limit is lower. Some even do not set a marriage age limit at all. From the perspective of progressive legal theory, a marriage age that is too low can violate human rights, especially the right of children to grow and develop optimally. Apart from that, a marriage age limit that is too low can also complicate efforts to protect women from domestic violence. Therefore, it is necessary to carry out further studies regarding the age limit for marriage in Indonesia. This study needs to consider aspects of justice and welfare and pay attention to the diversity of social and cultural conditions in Indonesia.